1981
DOI: 10.1210/jcem-53-4-828
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Weight Loss on Reproductive Hormones in Obese Men*

Abstract: The effects of weight reduction on reproductive hormones were investigated in 24 moderately obese men, 18-108% above ideal body weight. Serum estrone (E1), estradiol (E2), testosterone (T), percent free T (%FT), sex hormone binding globulin (SHBG) capacity, and, in 9 subjects, androstenedione (A) were measured serially before and during an outpatient supplemented fasting program (320 kcal/day) for 8-20 weeks. In the baseline state mean E1 was elevated to 100 +/- 7 pg/ml (normal, 30-60 pg/ml). The E2 was slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
4

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(66 citation statements)
references
References 28 publications
5
57
0
4
Order By: Relevance
“…In fact, although several studies reported the effects of weight loss on SHBG variation, a partial increase of SHBG was reported only by some of them, 3±5 whereas others failed to observe any signi®-cant variation, in spite of sustained weight loss. 6 Similar ®ndings were observed in obese women without clinical signs or symptoms of hyperandrogenism, in whom SHBG concentrations have been found unchanged 7 or slightly increased, 5 regardless of the degree of weight loss. Our data indicate, on the contrary, that changes of SHBG during weight loss largely depend on the amount of weight lost, at least in male subjects, and that normal SHBG concentrations can be achieved only in post-obese patient with near-normal body mass index.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In fact, although several studies reported the effects of weight loss on SHBG variation, a partial increase of SHBG was reported only by some of them, 3±5 whereas others failed to observe any signi®-cant variation, in spite of sustained weight loss. 6 Similar ®ndings were observed in obese women without clinical signs or symptoms of hyperandrogenism, in whom SHBG concentrations have been found unchanged 7 or slightly increased, 5 regardless of the degree of weight loss. Our data indicate, on the contrary, that changes of SHBG during weight loss largely depend on the amount of weight lost, at least in male subjects, and that normal SHBG concentrations can be achieved only in post-obese patient with near-normal body mass index.…”
Section: Discussionsupporting
confidence: 65%
“…Weight loss is usually followed by an increase of SHBG, 2±5 although contradictory results have been reported. 6,7 Recently, Strain and coworkers 4 suggested that in obese men losing weight, the increase of SHBG per unit decrease of BMI may be higher than that predicted on the basis of the pretreatment negative slope between SHBG and BMI. On the other hand it is not still clear whether weight loss may per se normalize SHBG concentrations nor how much weight an obese patient must lose to achieve SHBG concentrations similar to those of normal weight healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, urinary FSH levels increased dramatically during the fast, with no significant change in serum FSH levels, implying enhanced pituitary production (Klibanski et al, 1981). Other studies reported decreases in male reproductive hormone function during complete fasts, but many were confounded by obesity (Hoffer et al, 1986;Stanik et al, 1981), dehydration (Lee et al, 1977), and extreme psychological stress (Opstad, 1992).…”
Section: Caloric Deficienciesmentioning
confidence: 98%
“…Few randomized clinical studies have specifically evaluated the impact of diet and physical activity on testosterone levels in obese men. The results of these studies are essentially conflicting: some of them showed an increase of testosterone (26,27,28,29,30,31,32,33,34), others showed no change (35,36,37,38,39), and one small study has shown even a decrease in testosterone levels (40). Similarly, in the last 10 years, several trials have evaluated the impact of bariatric surgery on testosterone levels in men generally, showing an increase in testosterone levels (41,42,43,44,45,46,47,48).…”
Section: Introductionmentioning
confidence: 99%